Trends in death from circulatory diseases in Brazil between 1979 and 1996 - Mansur,Antonio de Padua (2001)
OBJECTIVE: To analyze the trends in mortality due to circulatory diseases in men and women aged > or = 30 years in Brazil from 1979 to 1996. METHODS: We analyzed population count data obtained from the IBGE Foundation and mortality data obtained from the System of Information on Mortality of the DATASUS of the Ministry of Health. RESULTS: Circulatory diseases, ischemic heart disease, and cerebrovascular disease were the major causes of death in men and women in Brazil. The standardized age coefficient for circulatory disease in men aged > or = 30 years ranged from 620 to 506 deaths/100,000 inhabitants and in women from 483 to 383 deaths/100,000 inhabitants for the years 1979 and 1996, respectively. In men, the mean coefficient for the period was 586.25 deaths with a significant trend towards a decrease (P<0.001) and a decline of 8.25 deaths/year. In women, the mean coefficient for the period was 439.58 deaths, a significant trend towards a decrease (P<0.001) and a rate of decline of 7.53 deaths/year. The same significant trend towards a decrease in death (P<0.001) was observed for ischemic heart disease and cerebrovascular disease. Risk of death from these causes was always higher for men of any age group (P<0.001). Cerebrovascular disease was the primary cause of death in women. CONCLUSION: Although circulatory diseases have been the major cause of mortality in men and women in the Brazilian population, with a greater participation by cerebrovascular diseases, a trend towards a decrease in the risk of death from these causes is being observed.